Suku Berber dan Transformasi Politik-Islami di Afrika Utara: Era Dinasti Al-Murabithun dan Al-Muwahidun - Romli, Hasbiyallah (UIN SIber Syekh Nurjati Cirebon, 2025)
This study aims to explore the contributions of the Berber people in the political transformation and strengthening of Islam in North Africa during the era of the Al-Murabitun and Al-Muwahhidun dynasties. Using a descriptive-analytical historical approach, the research examines the active role of the Berber people in the spread and reinforcement of Islam in the region. The findings indicate that the Berber people not only acted as mediators between Arab Muslims and local communities but also played a crucial role in establishing political, military, and intellectual structures that supported the dissemination of Islam. Additionally, cultural adaptation and the development of institutions such as mosques and madrasas further strengthened the presence of Islam in North Africa. Consequently, the study concludes that without the active participation of the Berber people, the Islamicization of North Africa would not have achieved significant success.